Incidence of Insect Pests on Chayote, Sechium edule (Swartz.) in Nepal - Neupane, FP; Sharma, MD; Neupane, KR (Journal of the Institute of Agriculture and Animal Science, 2006)
The insect pests recorded during 1993-96 on chayote in Chitwan, Lalitpur and Parbat districts were as follows: white grubs (Phyllophaga spp.), mole cricket (Gryllotalpa fussor Fab.), field cricket (Brachytrypes portentosus Licht.), red pumpkin beetle (Aulacophora foveicollis Lucas), blue pumpkin beetle (Aulacophora lewisii Baly), flea beetle (Monolepta signata Oliv.), tobacco caterpillar (Spodoptera litura Fab.), stink bug (Coridius janus Fab.), spotted beetle (Epilachna pusilanima Mulsant), banded blister beetle (Mylabris phalerata Pallas), brown bug (Agonoscelis nubila Fab.), cotton aphid (Aphis gossypii Glov.), pumpkin fruit fly (Bacterocera cucurbitae Coq.), and three unidentified insect pests- brown weevil, hairy caterpillars and stem boring beetle. Of them, the fruit fly and cotton aphid were the serious ones. Nepalese and Mexican accessions of chayotes varied for their susceptibility to both the above insects. The chayote fruits with tough fruit skin and dense and long spines were less susceptible to fruit fly, while the spineless and smooth fruits were the most susceptible. Key words: Chayote germplasm, insect pests, aphid and fruit fly J. Inst. Agric. Anim. Sci. 27:161-164 (2006)